Echolocation, as a method supporting spatial orientation and independent movement of people with visual impairment - MILER-ZDANOWSKA, KAMILA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Kamila Miler-Zdanowska, Echolocation, as a method supporting spatial orientation and independent movement of people with visual impairment. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 353-371. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.15 People with visual impairment use information from other senses to gain knowledge about the world around them. More and more studies conducted with the participation of visually impaired people indicate that data obtained through auditory perception is extremely important. In this context, the ability of echolocation used by blind people to move independently is interesting. The aim of the article is to present echolocation as a method supporting spatial orientation of people with visual impairment. The article presents the results of empirical studies of echolocation. It also presents the benefits of using this ability in everyday life and signals research projects related to the methodology of teaching echolocation in Poland. People with visually impaired to get knowledge about the world around them use information from other senses. Many studies conducted with the participation of visually impaired people indicate that data obtained through hearing are extremely important. In this context, the ability of echolocation used by blind people to move independently is interesting. The aim of the article is to present echolocation as a method supporting spatial orientation of people with visual disabilities. The article presents the results of empirical studies on echolocation. It also presents the benefits of using this skill in everyday life and signals research projects on the methodology of teaching echolocation in Poland.